Saccharomyces cerevisiae gene ISW2 encodes a microtubule-interacting protein required for premeiotic DNA replication - Trachtulcová, P; Janatová, I; Kohlwein, S D; Hasek, J (Yeast (Chichester, England), 2000)
A molecular genetic characterization of the ORF YOR304W (ISW2), identified in a screen of a yeast lambdagt11 library using a monoclonal antibody that reacts with a 210 kDa mammalian microtubule-interacting protein, is presented in this paper. The protein encoded by the ORF YOR304W is 50% identical to the Drosophila nucleosome remodelling factor ISWI and is therefore a new member of the SNF2 protein family and has been recently entered into SDG as ISW2. Although not essential for vegetative growth, we found that the ISW2 gene is required for early stages in sporulation. The isw2 homozygous deletant diploid strain was blocked in the G(1) phase of the cell cycle, unable to execute the premeiotic DNA replication and progress through the nuclear meiotic division cycle. ISW2 expression from a multicopy plasmid had the same effect as deletion, but ISW2 expression from a centromeric plasmid rescued the deletion phenotype. In vegetatively growing diploid cells, the Isw2 protein was preferentially found in the cytoplasm, co-localizing with microtubules. An accumulation of the Isw2 protein within the nucleus was observed in cells entering sporulation. Together with data published very recently by Tsukiyama et al. (1999), we propose a role for the Isw2 protein in facilitating chromatin accessibility for transcriptional factor(s) that positively regulate meiosis/sporulation-specific genes.
Keywords: western blotting; Saccharomyces cerevisiae; Microtubules; molekulová hmotnost; geny hub; replikace DNA; DNA Replication; Blotting, Western; Fungal Proteins; Genes, Fungal; spory hub; imunohistochemie; Spores, Fungal; Immunohistochemistry; fungální proteiny; Molecular Weight; mikrotubuly